2013
DOI: 10.1007/s13197-013-1198-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinach powder on physico-chemical, rheological, nutritional and sensory characteristics of chapati premixes

Abstract: Effect of spinach powder on the physico-chemical, rheological, nutritional and sensory characteristics on chapati premixes was studied by incorporating spinach powder at different concentrations from 1 % to 10 % based on wheat flour. Addition of 5 % of spinach powder to wheat flour was found to be optimum for chapati preparation. Effect of incorporation of spinach powder on the alveo-consistographic, mixographic and pasting characteristics were studied. It was observed that peak viscosity, breakdown viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
4
18
0
2
Order By: Relevance
“…The substitution of 5% green spinach flour showed the highest acceptability. This is in accordance with Khan et al (2015) that substitution of 5% spinach flour in chapati, Indian food product, provides the highest taste acceptability. Substitutions of 0%, 2.5%, and 5% indicated the acceptance of biscuit texture that is not significantly different.…”
Section: Acceptabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…The substitution of 5% green spinach flour showed the highest acceptability. This is in accordance with Khan et al (2015) that substitution of 5% spinach flour in chapati, Indian food product, provides the highest taste acceptability. Substitutions of 0%, 2.5%, and 5% indicated the acceptance of biscuit texture that is not significantly different.…”
Section: Acceptabilitysupporting
confidence: 89%
“…The difference is seen in the 7.5% substitution, with a lower acceptance score. Khan et al (2015) stated that the highest acceptability of chapati texture is given by the substitution of 5%, while the acceptability was low for higher substitution.…”
Section: Acceptabilitymentioning
confidence: 99%
“…This variation could be attributed to the different grains used in MGPs which have different pasting temperatures (Sanaa and El-syed, 2006). Earlier, Khan et al (2015) also reported increase in pasting temperature with an increase in the level of non-wheat flour due to higher resistance of starch granules to swell. The peak viscosity decreased with the increase in the level of incorporation of MGP.…”
Section: Pasting Characteristicsmentioning
confidence: 79%
“…Earlier it was also reported [26] an increase in water absorption with the increase in pumpkin flour using Farinograph. Earlier workers also reported that addition of fiber increases water absorption in cookies and bread due to hydroxyl groups present in the fiber [27][28][29]. The time required for dough development to reach a dough consistency equivalent to 2,200 mb pressure (TPr) was increased from 154 to 320 sec.…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%